Understanding Africa's rural households and farming systems - Moock, Joyce Lewinger (Boulder : Westview Press, 1986)
This book examines the difficult problems of agriculture in Sub-Saharan Africa. This was done by the farming systems approach which aims to improve food production under adverse conditions through agronomic and social science research conducted on the farm.
Includes bibliographical references: p. 217-232.
lje 30/06/2017
Loans
Keywords: Family farms; Households; Rural families; Africa, Sub-Saharan